Peningkatan hasil belajar siswa melalui metode demostrasi dengan menggunakan alat peraga benda konkret pada materi kubus dan balok di kelas V-B SD N 200515 Perumnas Pijorkoling (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
The aim of the research is to improve Students’ learning result through demonstration method using props to the concrete objects in cube and beam materials At V-b class of SD N 200515 Perumnas Pijorkoling. This research is PTK which uses the cycle method. In this case, the researcher is the teacher and the teacher is as an observer. The instrument that will be used is an essay test. Based on the research result which is obtained is students’ learning results increased in cube and beam materials through the demonstration method using concrete objects teaching aids, it can be seen from the increase in the results of the average initial test scores for all students is 52.67 and 6 students passed the test with a percentage of 20% of 30 students. In the first cycle test for meeting 1 with an average score of all students is 68.83 and 15 students passed the test with a percentage of 50% of 30 students. In the first cycle test for meeting II with an average score of all students is 75.33 and 23 students passed with a percentage of 76.66% of 30 students. While in the second cycle test for meeting I with an average score of all students is 77.66 and 25 students passed the test with a percentage of 83.33% of 30 students. Based on the percentage of students’ pass score already have achieved what is required then, the research was stopped until the second cycle of meeting I.
Keywords: demonstration methods; props of concrete objects